Diagenesis of the first member of Canglangpu Formation of the Cambrian Series 2 in northern part of the central Sichuan Basin and its influence on porosity - Zou, Bing; Qu, Haizhou; Zhao, Rongrong; Zhang, Lianjin; Zhang, Yu; Ma, Zike; Zhang, Xingyu; Huang, Qinyang; Mo, Qianwen; An, Hongyi; Pei, Yu (Frontiers in Earth Science, 2023)
In this paper, taking the first Member of the Canglangpu Formation of the Cambrian Series 2 in the northern central Sichuan Basin as an example, the diagenesis and its influence on porosity are systemically studied based on the observations and identifications of cores, casts and cathodoluminescence thin sections. The results show that the rock types of the first member of Canglangpu Formation are various, including mixed rocks, carbonate rocks and clastic rocks. The specific lithology is dominated by sand-bearing oolitic dolomite, sandy oolitic dolomite, sparry oolotic dolomite and fine-grained detrital sandstone. At the same time, the Cang 1 Member has experienced five types of diagenetic environments, including seawater, meteoric water, evaporative seawater, shallow burial, and medium-deep burial diagenetic environments. Moreover, the main diagenetic processes under different diagenetic environments include cementation, dissolution, compaction, chemical compaction, dolomitization and structural fractures. According to the analysis, fabric-selective dissolution in meteoric water diagenetic environment, dolomitization in evaporative seawater environment, and non-fabric-selective dissolution, dolomitization and structural fractures in buried diagenetic environment are beneficial to the development of pores. However, cementation, compaction and chemical compaction in medium and deep burial environments, are unfavorable for the development of pores.